Mental Health Effects on Job Retention in Indonesia - Arizal, M.; Wisana, I Dewa Gede Karma (Universitas Airlangga, 2023)
This study examines the effect of mental health proxied by depression on job retention. The primary independent variable is the change in depression scores in 2007 and 2014. It discovers the number of individuals whose depression scores remained, decreased, and increased. The dependent variable was being employed or unemployed in 2014. The data used in this study are from the Indonesia Life Family Survey (IFLS). The method used is logistic regression. The test results from 9675 observations showed that individuals who experienced symptoms of depression in the previous period decreased their work retention by 5.55%. Both men and women in this study showed significant results. This study confirms the long-term effect of depressive disorders on job retention.